History of the discovery of the etiological agent of Kaposi’s sarcoma – Human Herpesvirus 8, and the role of the Instituto Adolfo Lutz in researching this infection/ disease - Caterino-de-Araujo, Adele (2024)
In the year in which we celebrate 30 years since the discovery of the etiological agent of Kaposi's sarcoma (KS), at the time named Kaposi's sarcoma-associated herpesvirus (KSHV), later Human Herpesvirus 8 (HHV-8), the author reports on the role of the Instituto Adolfo Lutz in searching this agent using molecular biology techniques, first in biopsy material stored in paraffin and then in blood, saliva and urine, and in the characterization of subtypes and viral variants of HHV-8 that circulated in patients with KS associated with AIDS (KS-AIDS) in São Paulo, and in indigenous populations from the Brazilian Amazon. Furthermore, in-house serological techniques (indirect immunofluorescence and Western blotting) were standardized using cell lines containing HHV-8 in the latent and lytic phases of viral infection as antigens, and serum or blood collected on filter membrane to search for specific antibodies. The best cost/benefit serological and molecular tests were selected and employed in epidemiological surveys, and HHV-8 prevalence rates were determined in different populations: children, health professionals, individuals with HIV/AIDS, female sex workers, endemic and epidemic KS cases, Amerindians, individuals with chronic renal failure, and the general population of Mozambique. Based on studies related to the pathogenesis of HHV-8 and its association with HIV/AIDS, it was observed that the antiretroviral therapy prevented the emergence of KS-AIDS cases in Brazil and suggested its use to control KS-AIDS in Africa. Finally, HHV-8 infection was confirmed in a case of peripheral effusion lymphoma (PEL). Keywords: KSHV, HHV-8, diagnosis, prevalence, viral subtypes, Kaposi’s sarcoma.